EFFICACY TEST OF LIME LEAF ETHANOL EXTRACT (Citrus aurantifolia) AGAINST Aedes aegypti LARVAE - Isfanda Isfanda; Elita Agustina; Rizky Ahadi (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2023)
The primary carrier of the dengue virus-caused disease dengue hemorrhagic fever is the Aedes aegypti mosquito.By eliminating the flick using larvacides, the effort of seeding can be avoided. Tannin concentration in lime leaf extract (Citrus aurantifolia) is known to suppress the growth of larval cuticles. The objective of the study was to assess how C.aurantifolia lime leaf extract affected the development of Ae. aegypti larvae. This form of research is experimental, and this extract is produced by macerating lime leaves in 90% ethanol before extracting it via evaporation. The study included four groups: aquades used as a negative control for testing on larvae and concentrations of 12.5%, 25%, and 50% lime leaf extract. Testing and observations have been conducted for 24 hours. The findings showed that different concentrations of lime leaf ethanol extract (C. aurantifolia), which is 100% poisonous to Ae. aegypti larvae, can impede its growth. To conclude, biolarvasida can be created by using the lime leaf extract. No morphological modifications were made to the Ae. aegypti larvae used in this investigation.